The effect of APOL1 risk variants on emergent outcomes in kidney disorders: A meta-analysis of individual participant data - Amiri, Fateme Shamekhi (Ukrainian Journal of Nephrology and Dialysis, 2020)
Abstract. Kidney diseases associated with APOL1 polymorphisms are human immunodeficiency virus-associated nephropathy, idiopathic focal segmental glomerulosclerosis, hypertension-attributed chronic kidney disease, lupus nephritis and sickle cell nephropathy. This research aimed to investigate the risk of genetic variants on disease contribution. Methods. In this individual participant data meta-analysis, eighteen patients with kidney dysfunction and at risk of APOL1 genotype were investigated. Clinical features, laboratory data at initial presentation, management and outcomes were collected. The paper has written based on searching PubMed Central and Google Scholar to identify potentially relevant articles. Median, percentage, mean ± standard deviation (SD), two-tailed t and chi-square tests were used for statistical analyses. Moreover, relative risk, odds ratio for statistical analyses were used. Results: The average age of patients at the time of diagnosis in APOL1-associated kidney disorders was 41.09 ± 20.63 years (ranging from 8 years to 70 years). Relative risk for kidney failure and persistent hemodialysis therapy in APOL1-associated nephropathy patients with renal risk variants (RRVs) were assessed 1.13 and odds ratio of 1.5 with 95% CI of 0.08-26.86 and the value of 0.0764 by chi-square test but there was no significant statistical result in this research (p-value of 0.782). The relative risk for patients of allograft failure with RRVs was assessed 1,0 odds ratio of 1,0 95% CI of 0.06-15.99 and p-value of 0.81. Conclusion: The present study revealed the risk and odds of APOL1 gene effect on the onset of kidney failure with replacement therapy in patients at risk of APOL1 genotype but results were not significant statistically. Future clinical research is required for investigating APOL1 gene effect on non-African ancestry.